Pragmatic, constructive, and reconstructive memory influences on the hindsight bias - Salmen, Karolin; Ermark, Florian; Fiedler, Klaus (Psychonomic bulletin & review, 2023)
In hindsight, when the outcome of an uncertain scenario is already known, we typically feel that this outcome was always likely; hindsight judgments of outcome probabilities exceed foresight judgments of the same probabilities without outcome knowledge. We extend prior accounts of hindsight bias with the influence of pragmatic communication inherent in the task and the consolidation of self-generated responses across time. In a novel 3 × 2 within-participants design, with three sequential judgments of outcome probabilities in two scenarios, we replicated the within-participants hindsight bias observed in the classic memory design and the between-participants hindsight bias in a hypothetical design simultaneously. Moreover, we reversed the classic memory design and showed that subjective probabilities also decreased when participants encountered foresight instructions after hindsight instructions, demonstrating that previously induced outcome knowledge did not prevent unbiased judgments. The constructive impact of self-generated and communicated judgments (“saying is believing”) was apparent after a 2-week consolidation period: Not outcome knowledge, but rather the last pragmatic response (either biased or unbiased) determined judgments at the third measurement. These findings highlight the short-term malleability of hindsight influences in response to task pragmatics and has major implications for debiasing.